La unión de hecho en el Perú, los derechos de sus integrantes y desafíos pendientes - Zuta Vidal, Erika Irene (2018)
This article analyzes the regulation of common law marriage in Peru from its beginnings to the present. It focuses on its evolution, from a null recognition of rights and even violation of the fundamental rights of children born within a cohabitation, to its constitutional regulation and the consecration of the principle of equality. Starting from considering common law marriage as a source of family and examining its most important elements, the rights that concubines have been acquiring, either normatively or at a jurisprudential level, as well as addressing pending challenges.